Acupuncture treatment for optic atrophy: A protocol for systematic review. Issue 33 (August 2019) - Zhou, Ping-ping; Sun, Peng; Liu, Hong-wei; Meng, Yan
Abstract: Background: Optic atrophy (OPA) is a very tricky disorder. Presently, no effective management is available for this condition. Previous studies have reported that acupuncture may be effective for the treatment of OPA. However, its effectiveness is still inconclusive. Thus, this study will aim to assess the effectiveness and safety of acupuncture for OPA. Methods: A comprehensive literature search for relevant studies will be performed from the databases of PUMBED, EMBASE, CINAHI, Cumulative Index to Nursing and Allied Health Literature, Allied and Complementary Medicine Database, Cochrane Library, Chinese Biomedical Literature Database, China National Knowledge Infrastructure, and other literature sources from inception up to the present. No language limitations will be applied to all literature searches. We will consider all randomized controlled trials (RCTs) and case-controlled trials (CCTs) for assessing the effectiveness and safety of acupuncture for OPA. The primary outcomes include the rates of vision improvement and visual field improvement. The secondary outcomes consist of the increased visual field average sensitivity, pattern visual evoked potential (PVEP) amplitude, and shortened PVEP latency, as well as any expected and unexpected adverse reactions. Risk of bias assessment will be performed by Cochrane risk of bias for RCTs and Newcastle-Ottawa Scale for CCTs. Results: In this study, we will outline details of the aims and methods on the effectiveness and safety of acupuncture for the treatment of OPA. Conclusion: The results of this study will summarize the most current evidence of acupuncture for the treatment of patients with OPA. Dissemination and ethics: The results of this study are expected to be published on peer-reviewed journals. This is a literature-based study; therefore, no ethical approval is necessary. Systematic review registration: PROSPERO CRD42019135785